2023
DOI: 10.1159/000529415
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase A2 Receptor Antibodies and Clinical Prognosis in Patients with Idiopathic Membranous Nephropathy: An Updated Systematic Review and Meta-Analysis

Abstract: Background: Idiopathic membranous nephropathy (IMN) is the most common form of primary nephrotic syndrome in adults. Antibodies against the M-type phospholipase A2 receptor (PLA2R-ab) are considered as diagnostic biomarkers of IMN. Objective: Here, we performed an updated meta-analysis to assess the diagnostic value of PLA2R-ab for clinical remission in IMN patients. Method: PubMed, Embase and Cochrane databases were searched for relevant studies published before September 2022. Odds ratios (ORs) and correspon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
0
5
0
1
Order By: Relevance
“…The black and gray points are the optimal points determined by the maximum Youden's index (sensitivity + specificity-1); on the two points, the estimated probability of NR and UACR diurnal variation rate (%) was 0.331 and 58.5%. NR no remission, UACR urine albumin-to-creatinine ratio spontaneous remission rate were significantly declined in IMN patients with the highest titer [44], indicating that the quantitative measures may be required for prognosis prediction purpose. However, in the present study, even when the titer of anti-PLA2R was incorporated into the univariable logistic regression model, no significant difference was found (odds ratio 2.133 with 95% CI 0.649-7.009, P = 0.212).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The black and gray points are the optimal points determined by the maximum Youden's index (sensitivity + specificity-1); on the two points, the estimated probability of NR and UACR diurnal variation rate (%) was 0.331 and 58.5%. NR no remission, UACR urine albumin-to-creatinine ratio spontaneous remission rate were significantly declined in IMN patients with the highest titer [44], indicating that the quantitative measures may be required for prognosis prediction purpose. However, in the present study, even when the titer of anti-PLA2R was incorporated into the univariable logistic regression model, no significant difference was found (odds ratio 2.133 with 95% CI 0.649-7.009, P = 0.212).…”
Section: Discussionmentioning
confidence: 99%
“…However, no significant difference in the presence of anti-PLA2R-positive rate or the titer of anti-PLA2R was found among the three groups in this study ( P = 0.425 and 0.798, respectively). A meta-analysis indicated that compared to patients with the lowest titer of anti-PLA2R, the CR and spontaneous remission rate were significantly declined in IMN patients with the highest titer [ 44 ], indicating that the quantitative measures may be required for prognosis prediction purpose. However, in the present study, even when the titer of anti-PLA2R was incorporated into the univariable logistic regression model, no significant difference was found (odds ratio 2.133 with 95% CI 0.649–7.009, P = 0.212).…”
Section: Discussionmentioning
confidence: 99%
“…It is primarily caused by antibodies targeting the antiphospholipase A2 receptor (PLA2R), resulting in the accumulation of immune complexes in the glomerular basement membrane (32). Recent research has shown that patients who test positive for PLA2R antibodies experiencing a reduced rate of natural remission compared to individuals who test negative for antibodies (33).Standard therapies, including corticosteroids and cyclophosphamide, may not achieve immunologic remission in approximately 10% of patients with membranous nephropathy associated with anti-phospholipase A2 receptor antibody (aPLA2R). Research has shown that the blend of rituximab, cyclophosphamide, and corticosteroids in a cycle therapy approach has proven to be highly effective.…”
Section: Membranous Nephropathymentioning
confidence: 99%
“…Первичная мембранозная нефропатия, являющаяся основной причиной НС у людей старшего возраста (пик заболеваемости в возрасте 40-60 лет), встречается в несколько раз чаще (70-80% случаев) вторичной нефропатии, которая развивается при аутоиммунных заболеваниях (прежде всего СКВ), злокачественных опухолях, инфекциях и под действием лекарственных средств [14]. Примерно у 80% пациентов с первичной мембранозной нефропатией обнаруживают IgG4-антитела к подоцитарному трансмембранному рецептору фосфолипазы А2 М-типа (PLA2R), высокий титр которых ассоциируется с развитием НС, повышенным риском хронической почечной недостаточности и ухудшением ответа на иммуносупрессивную терапию [15]. Кроме того, наличие антител к PLA2R подтверждает диагноз первичной мембранозной нефропатии и позволяет планировать лечение без его гистологической верификации [8].…”
Section: морфологические варианты поражения почек сопровождающегося н...unclassified